Prevalence and risk factors of sarcopenia without obesity and sarcopenic obesity among Chinese community older people in suburban area of Shanghai: A cross-sectional study - Lu, Linqian; He, Xiangfeng; Song, Yanping; Zhuang, Min; Wu, Xie; Chen, Nan (Frontiers in Aging Neuroscience, 2022)
Objectives: To explore the prevalence and risk factors of sarcopenia without obesity (S) and sarcopenic obesity (SO) among community-dwelling older people in the Chongming District of Shanghai, China. Methods: A total of 1407 subjects aged ≥ 65 years old were included, mean age was 71.91 ± 5.59 years old and mean body mass index (BMI) was 24.65 ± 3.32 kg/m2. According to the Asian Working Group for Sarcopenia 2019 Consensus, sarcopenia was defined as low appendicular skeletal muscle mass index (≤ 7.0 kg/m2 in males and ≤ 5.7 kg/m2 in females), decreased handgrip strength (< 28.0 kg in males and < 18.0 kg in females) and/or low gait speed (< 1.0 m/s) or poor 5-time chair stand test (≥ 12s). SO met both diagnostic criteria for sarcopenia and obesity, meanwhile obesity was defined as an increased percentage of body fat (PBF) (≥ 25% in males and ≥ 35% in females). Univariate and multiple logistic regression analyses were applied to explore the risk factors of S and SO. Results: The prevalence of S and SO were 9.74% (M: 9.29%, F: 10.05%) and 9.95% (M: 13.94%, F: 7.14%). Lower BMI (OR=0.136, 95% CI: 0.054-0.340, p<0.001), lower hip circumference (OR=0.858, 95% CI: 0.816-0.903, p<0.001), farming (OR=1.632, 95% CI: 1.053-2.530, p=0.028), higher high-density lipoprotein cholesterol level (OR=2.235, 95% CI: 1.484-3.367, p<0.001) and a sleep duration < 7 h (OR=0.561, 95% CI: 0.346-0.909, p=0.019) were risk factors for S. For SO, aging (70-74 y, OR=1.923, 95% CI: 1.122-3.295, p=0.017; 75-79 y, OR=3.185, 95% CI: 1.816-5.585, p<0.001; ≥ 80 y, OR=7.192, 95% CI: 4.133-12.513, p<0.001), male (OR=1.981, 95% CI: 1.351-2.904, p<0.001), higher BMI (OR=4.865, 95% CI: 1.089-21.736, p=0.038), higher monocytes level (OR=4.203, 95% CI: 1.340-13.181, p=0.014) and a sleep duration > 9 h (OR=1.881, 95% CI: 1.117-3.166, p=0.017) were risk factors. Conclusion: Our study showed the high prevalence of S and SO among community-dwelling older people in the Chongming District. SO was more prevalent in males. Behavioral factors and lifestyle (such as farming and sleep duration) were more associated with the development of S, while age and male were more associated with the development of SO.